Solar energy utilization and efficiency of an oak forest in the Vakarel mountains - Ljubenova, Mariana (Macedonian Journal of Ecology and Environment, 1994)
Results of energy reserves in the above-ground and bellow-ground phytomass of the Quercus frainetto+Quercus cerris - Festuca heterophylla+Poa nemoralis association were analyzed. The annual accumulation and the efficiency coeficient of the association were evaluated.